KEBIJAKAN PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM MENGATASI PENAMBANGAN EMAS ILEGAL DI KECAMATAN SINGINGI HILIR - M. Al Haudrye Nst; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Mining activities in Indonesia still receive a negative stigma among the community, especially in Singingi Hilir District, Kuantan Singingi Regency, this is due to illegal mining activities or mining without permits which result in more negative impacts. So far, gold mining activities without a permit in Kuantan Singingi Regency, especially Singingi Hilir Subdistrict, have not been disciplined and are directed to have a permit from the local government. Various efforts made by the Kuantan Singingi Regency Government have not been able to overcome illegal mining activities including conducting socialization and counseling and controlling mining activities to avoid the negative impacts caused by these illegal mining activities, Based on these problems, the authors are interested in knowing first, how are local government policies in overcoming Illegal Gold Mining in Singingi Hilir District? Second, what are the obstacles faced by the local government in controlling Illegal Gold Mining in Singingi Hilir District? Third, what are the efforts made by the local government in controlling Illegal Gold Mining in Singingi Hilir District?Based on the results of the research and discussion, it can be concluded that, firstly, the Regional Government Policy in Overcoming Illegal Gold Mining in Singingi Hilir District by forming an Integrated Team for Controlling Unlicensed Gold Mining (PETI) in charge of socializing, and controlling mining sites. The two obstacles of the Regional Government in Its Policy to Overcome Illegal Gold Mining in Singingi Hilir District include the lack of awareness of the local community towards the law and the environment as well as the presence of irresponsible individuals who back up the PETI activities and the absence of a local regulation that regulates PETI in the District. Kuantan Singingi. Third, Efforts to maximize Local Government Policies in overcoming Illegal Gold Mining in Singingi Hilir District include direct control of PETI locations and socialization to the public about the impact of PETI on the environment in order to increase public awareness.Keywords : Policy - Government - PETI